MECANISMOS DE LESIÓN CEREBRAL EN NIÑOS PREMATUROS. - CERISOLA, ALFREDO; BALTAR, FEDERICO; FERRÁN, CEILA; TURCATTI, EMILIO (Medicina (Buenos Aires))
Preterm birth is one of the main country health indicators. It is associated with high mortality and significant morbidity in preterm newborns with cerebral palsy and potential long-term neurodevelopmental disabilities like cognitive and learning problems. The main lesions could be: a) white matter injuries, generally associated with cortical and other regions of grey matter neuronal-axonal disturbances; b) intracranial hemorrhage that includes germinal matrix, intraventricular and parenchymal, c) cerebellum injuries. The white matter lesions include cystic and non-cystic (with microscopic focal necrosis) periventricular leukomalacia and non-necrotic diffuse white matter injury. Multiple etiologic factors are associated with these injuries. Anatomical and physiological characteristics of periventricular vascular structures predispose white matter to cerebral ischemia and, interacting with infection/inflammation factors, activate microglia, generating oxidative stress (mediated by free oxygen and nitrogen radicals), pro-inflammatory cytokine and glutamate toxicity, energetic failure and vascular integrity disturbances. All these factors lead to a particular vulnerability of pre-oligodendrocytes that will affect myelination. Hypoxia-ischemia also may produce selective neuronal necrosis in different cerebral regions. Germinal matrix is a highly vascularized zone beneath ependymal or periventricular region that constitutes a capillary bed with a particular structural fragility that predispose it to hemorrhage.